3 or 3′-Galloyl substitution plays an important role in association of catechins and theaflavins with porcine pancreatic α-amylase: The kinetics of inhibition of α-amylase by tea polyphenols. (October 2016) - Sun, Lijun; Warren, Fredrick J.; Netzel, Gabriele; Gidley, Michael J.
Highlights: α-Amylase activity was inhibited by three tea extracts and phenolic compounds in teas. Only catechins with a galloyl substituent at the 3-position showed measurable inhibition. 3 and 3′ Galloyl substitution increase the inhibitory activity of theaflavins. 3 or 3′ Galloyl substitution increase the association of catechins and theaflavins with amylase. There is a linear correlation between IC50 and inhibition constants ( Kic and Kiu ). Abstract: The inhibitory activities of three tea extracts (TEs) and individual phenolic compounds in TEs against porcine pancreatic α-amylase (PPA) were studied by measuring their half inhibitory (IC50 ) concentrations. The kinetics of inhibition by these extracts and compounds were investigated through Dixon, Cornish-Bowden, and Lineweaver–Burk plots. The results showed that green, oolong and black tea extracts, epigallocatechin gallate, theaflavin-3, 3′-digallate and tannic acid were competitive inhibitors of PPA, whereas epicatechin gallate, theaflavin-3′-gallate and theaflavin were mixed-type inhibitors with both competitive and uncompetitive inhibitory characteristics. Only catechins with a galloyl substituent at the 3-position showed measurable inhibition. The competitive inhibition constants ( Kic ) were lower for theaflavins than catechins, with the lowest value for theaflavin-3, 3′-digallate. The lower Kic than the uncompetitive inhibition constant for the mixed-type inhibitors suggests that they bind more tightly with free PPA than with the PPA–starch complex. A 3 and/or 3′-galloyl moiety in catechin and theaflavin structures was consistently found to increase inhibition of PPA through enhanced association with the enzyme active site.